2023
DOI: 10.1021/acs.cgd.3c00194
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Bonding as a Promoter of Crystalline Diversity in Halogenated [2]Rotaxanes

Abstract: Understanding the nature of the mechanical bond is critical to advancing the design of novel mechanically interlocked molecules. Given that numerous applications of new materials are related to solid-state properties, the behavior of the mechanical bond in the crystalline solid state is a key issue to be explored. Hence, this study sought to address how the freedom degree of the interlocked components can promote the formation of different crystalline phases. A series of rotaxanes substituted with different ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 45 publications
(110 reference statements)
1
9
0
Order By: Relevance
“…Thus, higher RMS values might imply a more pronounced supramolecular crystalline organization. Both compounds 2 and 3 exhibit nearly identical average RMS values, underscoring their molecular and supramolecular similarities, as previously discussed elsewhere …”
Section: Resultssupporting
confidence: 77%
See 2 more Smart Citations
“…Thus, higher RMS values might imply a more pronounced supramolecular crystalline organization. Both compounds 2 and 3 exhibit nearly identical average RMS values, underscoring their molecular and supramolecular similarities, as previously discussed elsewhere …”
Section: Resultssupporting
confidence: 77%
“…Studies by our research group have consistently demonstrated solvate formation in rotaxane molecules. ,, , As part of our ongoing projects, we came across an interesting case through crystallization assays: two crystalline structures were found for a rotaxane molecule ( 1 ), one as a hydrate form ( 1I ) and the other in an anhydrous form ( 1II ) (Figure ). Our recent investigation exploring the crystalline diversity in halogenated [2]­rotaxanes revealed similar cases featuring pairs and trios of anhydrous and solvate forms of [2]­rotaxanes . Instigated by these results, we sought to understand the intricacies surrounding solvate formation in rotaxane molecules.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…By inspecting the Hirshfeld surface analysis of 3 and 4 , mainly potential hydrogen bonding sites at the rim are observed, therefore 3 and 4 resemble hydrogen‐bonded polypseudorotaxanes [34–35] in the solid state. These new findings, that the variation of guest molecules to encapsulate into pillarplexes can strongly influence the packing and the occurring (non–)covalent interactions, makes those mechanically‐interlocked molecules interesting in the context of recently introduced hydrogen‐bonded frameworks (HOFs) [36–39] and in the context of crystal engineering [40] …”
Section: Resultsmentioning
confidence: 99%
“…These new findings, that the variation of guest molecules to encapsulate into pillarplexes can strongly influence the packing and the occurring (non-)covalent interactions, makes those mechanically-interlocked molecules interesting in the context of recently introduced hydrogen-bonded frameworks (HOFs) [36][37][38][39] and in the context of crystal engineering. [40]…”
Section: Crystallographic Analysismentioning
confidence: 99%